Haematological manifestations of COVID‐19: From cytopenia to coagulopathy. (31st August 2020) - Agbuduwe, Charles; Basu, Supratik
Abstract: Emerging data from the management of patients with coronavirus disease 2019 (COVID‐19) suggests multi‐systemic involvement, including the hemopoietic system. The haematological manifestations of COVID‐19 include blood count anomalies notably lymphopenia and neutrophilia which are of prognostic significance. Hyperferritinemia and elevated lactate dehydrogenase have also been associated with increased mortality. Furthermore, there is considerable evidence of a distinct coagulopathy associated with COVID‐19 characterised by elevated D‐dimers and an increased risk of thrombotic events. This comprehensive review summarises the latest evidence from published studies and discusses the implications of the various haematological manifestations of COVID‐19 with a view to guiding clinical management and risk stratification in this rapidly evolving pandemic.